Designing nanographitic domains in N-doped porous carbon foam for high performance supercapacitors. (November 2018) - Ni, Ling; Wang, Runwei; Wang, Hongbin; Sun, Chuanyin; Sun, Bing; Guo, Xin; Jiang, Shang; Shi, Zhiqiang; Jing, Wendan; Zhu, Liangkui; Qiu, Shilun; Zhang, Zongtao
Abstract: Porous carbon with high surface area and low cost has emerged as promising alternative electrode for supercapacitor. However, the poor electrical conductivity arising from the rich existence of sp 3 carbon remains a big challenge. Here, a novel strategy is reported for the nanographitic domains (sp 2 carbon) distributed in porous carbon via transition metal acetate (M(CH3 COO)2 M = Fe, Co, Ni) assistance and in situ N-doping during the activation process. The resultant different N-doped porous carbon foams (denoted as NCF (Fe), NCF (Co), NCF (Ni)) exhibit a localized graphitic structure and hierarchically porous framework with micropore integrating into macroporous scaffold. Whereas, the NCF (Fe) shows ultra-high BET surface areas of up to 2630 m 2 g −1, a large pore volume of up to 1.1 cm 3 g −1, notable nitrogen content of 5.34 wt %, optimal pore size and superior hydrophilicity. When adopted as supercapacitor electrode, the NCF (Fe) presents a reversible capacity of 273.7 F g −1 in 6 M KOH aqueous electrolyte. Even at a high current of 10 A g −1, a capacity of 200.5 F g −1 can also be achieved, which makes it a potential capacitive material for high-rate supercapacitor. Considering other advantages of the method such as cheap precursor, facile process et al., NCF (Fe) can be rendered to be a promising candidate for commercial supercapacitors. Graphical abstract: Image